LncRNAs and their RBPs: How to influence the fate of stem cells? - Cong Zhao; Wen Xie; Hecheng Zhu; Ming Zhao; Weidong Liu; Zhaoping Wu; Lei Wang; Bin Zhu; Shasha Li; Yao Zhou; Xingjun Jiang; Qiang Xu; et al. (Stem Cell Research & Therapy, 2022)
Abstract Stem cells are distinctive cells that have self-renewal potential and unique ability to differentiate into multiple functional cells. Stem cell is a frontier field of life science research and has always been a hot spot in biomedical research. Recent studies have shown that long non-coding RNAs (lncRNAs) have irreplaceable roles in stem cell self-renewal and differentiation. LncRNAs play crucial roles in stem cells through a variety of regulatory mechanisms, including the recruitment of RNA-binding proteins (RBPs) to affect the stability of their mRNAs or the expression of downstream genes. RBPs interact with different RNAs to regulate gene expression at transcriptional and post-transcriptional levels and play important roles in determining the fate of stem cells. In this review, the functions of lncRNAs and their RBPs in self-renewal and differentiation of stem cell are summarized. We focus on the four regulatory mechanisms by which lncRNAs and their RBPs are involved in epigenetic regulation, signaling pathway regulation, splicing, mRNA stability and subcellular localization and further discuss other noncoding RNAs (ncRNAs) and their RBPs in the fate of stem cells. This work provides a more comprehensive understanding of the roles of lncRNAs in determining the fate of stem cells, and a further understanding of their regulatory mechanisms will provide a theoretical basis for the development of clinical regenerative medicine.